Influence of Using a Contrast-Enhanced CT Image as the Primary Image on CyberKnife Brain Radiosurgery Treatment Plans - Zhang, Jianping; Wang, Lin; Xu, Benhua; Huang, Miaoyun; Chen, Yuangui; Li, Xiaobo (Frontiers in Oncology, 2021)
Background and purpose: This study aimed to quantify the differences between pre- and post-contrast agent (CA) CT for Cyberknife brain SRS plans. Materials and Methods: Twenty-five patients were retrospectively analyzed. They were divided into two categories, inhomogeneous cases (13 patients) and homogeneous cases (12 patients), according to whether the tumor was close to the cavity and inhomogeneous tissues or not. The pre-CA and post-CA plans were designed and calculated using the same monitor unit and paths as those in the ray-tracing algorithm, respectively. Results: The CT number difference of tumor between pre- and post-CA was significant (in average, 24.78±18.56 HU, P-value < 0.01). The deviation value of the target was largest at approximately 37 HU (Inhomo-) and 13 HU (Homo-) (p<0.01), and the values of the OARs were not statistically significant (P-value >0.05). It was not nevertheless statistically significant for the dose difference between two groups with the injection of CA (P-value >0.05). The absolute effective depth difference generally remained at a level of 1mm, but the dose difference was quietly fluctuated sometimes more than 20%. The absolute effective depth difference of the Inhomo-case (0.62 mm) was larger than that of the Homo-case (0.37 mm) on median, as well as the variation amplitude (P-value<0.05). And the relative dose differences between the two cases were 0.38% (Inhomo-) and 0.2% (Homo-), respectively (P-value<0.05). At the criterion of 1 mm/1%, the gamma pass rate of the Homo-case (95.89%) was larger than that of the Inhomo-case (93.79%). For the OARs, except for the cochlea, the two cases were almost the same (>98.85%). The tumor control probability of the target was over 99.99% before and after injection of a CA, as well as the results for the Homo-case and Inhomo-case. Conclusions: Considering the difference of evaluation indexes between pre- and post-CA images, we recommended the plain CT was employed as the primary image for improving the CK treatment accuracy of brain SRS, especially when the target was close to CA-sensitive, OARs and cavity.